Предмет: Математика,
автор: mimimi3978
Решите пожалуйста уравнение :
6-3(х+1)=7-х
Ответы
Автор ответа:
0
Ответ: х= - 2
Пошаговое объяснение:
6-3(х+1)=7-х
6- 3х -3=7 - х
-3х+х=7- 6 +3
-2х= 4
х=4:(-2)
х=-2
-------------
6-3(-2+1)=7-(-2)
6- 3(-1)=7+2
6+3=9
9=9
Автор ответа:
0
6-3(х+1)=7-х
6-3х-3=7-х
-3х+х=7-6+3
-2х=4
х=4/(-2)
х=-2
ОТВЕТ: -2
6-3х-3=7-х
-3х+х=7-6+3
-2х=4
х=4/(-2)
х=-2
ОТВЕТ: -2
Похожие вопросы
Предмет: Алгебра,
автор: dsevcenko006
Предмет: Литература,
автор: Аноним
Предмет: Химия,
автор: 08022022vrsmart
Предмет: Математика,
автор: Alexander711
Предмет: История,
автор: maksiimandriev1